Uncertainty analysis in the assessment of long-term noise indicators - Batko, W.; Bal-Pyrcz, R. (Archives of Acoustics, 2006)
This study addresses the assessment conditions of long-term noise indicators based onirregular noise monitoring data. Variations of $L_{ DEN}$ estimates (day – evening – night noiseindicator) on different days of the week were examined. Two hypotheses are verified: thatmean estimates shall be identical on all days of the week and that variances of thus obtainedestimates are homogeneous. The data for statistical analyses were noise levels recorded in oneyear by an on-line noise monitoring system in Kraków.